2021
DOI: 10.1093/ndt/gfab185
|View full text |Cite
|
Sign up to set email alerts
|

Serum hemoglobin concentration and risk of renal function decline in early stages of diabetic kidney disease: a nationwide, biopsy-based cohort study

Abstract: Background Prognosticating disease progression in patients with diabetic kidney disease (DKD) is challenging, especially in the early stages of kidney disease. Anemia can occur in the early stages of kidney disease in diabetes. We therefore postulated that serum hemoglobin concentration, as a reflection of incipient renal tubulointerstitial impairment, can be used as a marker to predict DKD progression. Methods Drawing on nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…These findings showed anemia was indeed an independent risk factor for rapid eGFR decline in type 2 diabetic patients. A recent multicenter cohort study in Japan revealed that circulating Hb concentration, associated with tubulointerstitial injury, could be a predictor for DKD progression ( 37 ), which was consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…These findings showed anemia was indeed an independent risk factor for rapid eGFR decline in type 2 diabetic patients. A recent multicenter cohort study in Japan revealed that circulating Hb concentration, associated with tubulointerstitial injury, could be a predictor for DKD progression ( 37 ), which was consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have shown the greater risks of cardiovascular disease and kidney disease progression associated with low Hb levels. [24][25][26][27][28] Taken together, these findings underscore the importance of stable Hb control within the target Hb range. The increased risks of adverse clinical events even in the group whose Hb level was fluctuating around the lower limit of target Hb range suggest the importance of maintaining Hb level within the target range of Hb 11-13 g/dl.…”
Section: Discussionmentioning
confidence: 62%
“…In the present study, low Hb levels were associated with an increased risk of developing DKD. Although previous studies have demonstrated the predictive value of Hb for the risk of renal function decline in the early stages of DKD [43] , the negative association between baseline Hb concentrations and the risk of follow-up DKD has often been ignored [13,44] . We speculate that patients with diabetes often have anaemia, which can lead to renal hypoxia and accelerate the progression of diabetic nephropathy [45,46] .…”
Section: Discussionmentioning
confidence: 99%